Screening dan Manajemen Stres sebagai Upaya Peningkatan Kesehatan Mental Remaja - Liyanovitasari; Puji Lestari; Umi Setyoningrum (UNIVERSITAS NGUDI WALUYO, 2024)
Adolescence is a transition phase from childhood to adulthood. This transition process causes stress both physically and mentally for teenagers. Long-term stress can also affect adolescents' adaptation, giving rise to behavior such as attempting suicide (8.5%), sadness and despair (29%), drinking alcohol (45%), and using marijuana/drugs (22%). Progressive muscle relaxation is a technique for dealing with stress by tensing and relaxing the muscles to relax the muscles, relieve pain, anxiety, anxiety, increase comfort and concentration. This activity aims to increase teenagers' knowledge and skills in carrying out progressive muscle relaxation. Community service activities were carried out on Tuesday 5 March 2024. The target of this service program was students at the Sudirman Islamic Vocational School, Ungaran, attended by 40 students. The methods used in this activity are discussion, lecture, question and answer, demonstration and re-demonstration. Educational media are powerpoints, leaflets and videos of progressive muscle relaxation exercises. This activity was carried out in three stages, including the first stage of preparation by obtaining permission to go to the school, preparing media, conducting a pre-test, and conducting stress screening on students. The second stage of implementation is the delivery of educational material on the concept of stress and a demonstration of progressive muscle relaxation. The third stage is evaluation by conducting a post test on students. The measurement results showed that students' knowledge before being given stress management education increased from 2.6 to 5.8. In addition, students' ability in progressive muscle relaxation increased from 3.2 to 6.2. It is hoped that students can carry out progressive muscle relaxation independently so that stress can be overcome and can improve students' mental health. ABSTRAK Remaja merupakan fase transisi dari masa kanak-kanak menuju dewasa. Proses transisi ini menyebabkan stres baik secara fisik maupun mental remaja. Stres jangka panjang juga dapat mempengaruhi adaptasi remaja sehingga menimbulkan perilaku seperti percobaan bunuh diri (8,5%), sedih dan putus asa (29%), minum alkohol (45%), dan menggunakan ganja/narkoba (22%). Relaksasi otot progresif sebagai teknik mengatasi stres dengan menegangkan dan melemaskan otot untuk membuat otot menjadi rileks, meredakan nyeri, kecemasan, ansietas, meningkatkan kenyamanan dan konsentrasi. Kegiatan ini bertujuan untuk meningkatkan pengetahuan dan keterampilan remaja melakukan relaksasi otot progresif. Kegiatan pengabdian kepada masyarakat dilaksanakan pada hari Selasa 5 Maret 2024. Sasaran program pengabdian ini yaitu siswa SMK Islam Sudirman Ungaran diikuti oleh 40 siswa. Metode yang digunakan dalam kegiatan ini yaitu diskusi, ceramah, tanya jawab, demonstrasi, dan re-demonstrasi. Media edukasi adalah powerpoint, leaflet, dan video latihan relaksasi otot progresif. Kegiatan ini dilakukan dalam tiga tahap mencakup tahap pertama persiapan dengan melakukan perijinan ke sekolah, menyiapkan media, melakukan pre test, dan melakukan screening stres pada siswa. Tahap kedua pelaksanaan yaitu penyampaian materi edukasi konsep stres dan demonstrasi relaksasi otot progresif. Tahap ketiga adalah evaluasi dengan melakukan post test pada siswa. Hasil pengukuran bahwa pengetahuan siswa sebelum diberikan edukasi manajemen stres meningkat dari 2,6 menjadi 5,8. Selain itu kemampuan siswa dalam relaksasi otot progresif meningkat dari 3,2 menjadi 6,2. Diharapkan bagi siswa untuk dapat melakukan relaksasi otot progresif dengan mandiri agar stres dapat teratasi dan dapat meningkatkan kesehatan mental siswa.